2013
DOI: 10.1186/1749-7922-8-52
|View full text |Cite
|
Sign up to set email alerts
|

Children and adolescents deaths from trauma-related causes in a Brazilian City

Abstract: IntroductionInjury is the first cause of death worldwide in the population aged 1 to 44. In developed countries, the most common trauma-related injuries resulting in death during childhood are traffic accidents, followed by drowning.MethodsThis retrospective study based on autopsy examinations describes the epidemiology profile of deaths by trauma-related causes in individuals younger than 18 years from 2001 to 2008 in the city of Campinas. The aim is to identify epidemiology changes throughout the years in or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
11
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 33 publications
5
11
2
6
Order By: Relevance
“…Similar to our results, reports from Brazil and Lorestan showed that children older than 15 years had the highest mortality due to firearms (10,26). This may be explained by higher rates of retaliatory attitudes (32) and easier access to firearms (33) in children of this age category.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Similar to our results, reports from Brazil and Lorestan showed that children older than 15 years had the highest mortality due to firearms (10,26). This may be explained by higher rates of retaliatory attitudes (32) and easier access to firearms (33) in children of this age category.…”
Section: Discussionsupporting
confidence: 81%
“…On the contrary, our results showed that all cases of aspiration were accidental in infants and children up to five years. This is in concordance with reports from Brazil and Japan (4,26). Also, airway obstruction was the most common cause of injury -related mortality in a report from Tehran (27).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The study showed that epidemiology varies regarding the pattern of injuries. 1,[4][5][6][7][8][9][10][11][12][13] As study done by Chawdhury et al, 15 this study also revealed burns & electrical Injury (0.9%) as one of the causes of childhood injury. 14 Childhood injury by electrocution occurs when children are playing near electric equipments or near fire materials.…”
Section: Discussionmentioning
confidence: 65%